Development of a damage propagation analysis system based on level set XFEM using the cohesive zone model. (1st October 2016) - Nagashima, T.; Sawada, M.
Abstract: The level set extended finite element method (XFEM) is applied to two-dimensional and quasi-three-dimensional crack propagation analyses using cohesive zone models (CZMs). The proposed method uses no asymptotic basis functions near the crack tip and uses only the Heaviside function. The crack geometry is approximated by two signed distance functions (SDFs). Elements that include a crack are then classified into several partitioned patterns according to nodal SDF values, and enriched nodes are determined. A CZM is introduced to the crack line or the surface including a discontinuous displacement field modeled by XFEM. In order to solve the discretized governing equations, the implicit method and the explicit dynamic method are used. The proposed method is applied to the crack propagation analysis of a three-point bending beam and fracture analyses of carbon fiber reinforced plastic (CFRP) laminates considering the interaction between the matrix cracks and delamination.